Does Gender Matter While Enhancing Soil Health? - Gondwe, T.; Diabate, F.; Huyer, S. (2025)
Climate resilient agriculture is about improving people’s capacity for resilience through increasing the adaptability, and transformability of agricultural practices. Women play a crucial role in sustainable soil management (SSM) that ensures women’s empowerment including food, economic and social security and hence their role needs to be valued. Through the implementation of AICCRA, women have been involved in technologies that enhance soil health, such as bundling of capacity building activities with technologies, such as promoting the cultivation of legumes such as cowpeas in Ghana and promoting ‘Smart Valleys’ in Mali, involving both men and women for developing inland valleys for rice production. The approach offers a farmer-led alternative that optimizes water control, enhances soil fertility, and boosts productivity sustainably. Key lesson learnt is that provision of tailored training on soil health management approaches that takes into considerations men and women empowers women and contributes towards closing the gender productivity-gap.